Sustainable farm management practices for rice-fish co-cultivation in Arunachal Pradesh, India - Samaddar, Ayan; Bayan, Baban; Kacha, Dani (WorldFish, 2023)
This brief captures the assessment carried out in Arunachal Pradesh, India to assess rice-fish systems and it's effectiveness. Brief provides a narrative on how the system can be adopted and what are some potential benefits of this system.